Diagnostic yield from cardiac gene panel testing for inherited cardiac conditions in a large Irish cohort. (14th October 2021) - Murphy, J M; Kirk, C W; Galvin, J; Ward, D; Prendiville, T; Lynch, S A
Abstract: Background: Inherited cardiomyopathies (hypertrophic, dilated and arrhythmogenic) and cardiac ion channelopathies (long QT, Brugada and CPVT) predispose to sudden cardiac death/sudden arrhythmic death syndrome. Given their genetically heterogenous nature, multi-gene DNA sequencing panels are useful to aid genetic diagnosis. Purpose: Investigate the diagnostic yield from cardiac gene panel testing undertaken in patients (including molecular autopsy in deceased patients) referred to four clinical services from 2002 to 2020. Methods: Data was collected by interrogation of departmental databases, family charts, and review of molecular genetic diagnostic reports. Results: We evaluated molecular genetic diagnostic results from 835 individuals (461 males, 374 females) from 824 families, including 58 deceased patients who underwent molecular autopsy. The median age of the cohort was 44 years (range 0.1–86 years). Testing for hypertrophic cardiomyopathy (HCM) and long QT syndrome (LQT) genes represented 36% and 32% of the cohort, respectively, with the remaining 32% accounting for other cardiomyopathies, arrhythmia syndromes or metabolic/syndromic diseases. The overall variant detection rate was 50% across all panel types. Three hundred and fifty patients (42%) carried a single variant, 68 patients (8%) carried multiple variants (up to a maximum of four), including two individuals who carried two actionable (pathogenic/likely pathogenic) variants each and 30 individuals (5%) with one actionable variant plus a variant of uncertain significance (VUS). The overall diagnostic yield of at least one actionable variant was 28%. At least one VUS was detected in 27% of the cohort. Molecular autopsy yielded an actionable variant in 10% of patients, while 30% of the subcohort carried at least one VUS (up to maximum of two). We found a positive association between female sex and the likelihood of detecting an actionable variant. By decade of age, detection of actionable variants ranged from 19% (60–69 years) to 41% (0–9 years). By panel type, actionable variants ranged from 14% (Brugada) to 35% (cardiomyopathy). The burden of VUS ranged from 22% (LQT) to 46% (dilated cardiomyopathy). Altogether 234 actionable variants were detected in 26 genes, including seven metabolic or syndromic disease genes. From those with non-metabolic/syndromic forms of disease, 84% of actionable variants were detected in well established ICC genes. Analysis of gene-disease associations for VUS detected from HCM and LQT panels revealed that 10–25% were detected in genes now deemed to have only moderate or limited evidence of disease causation. Conclusion: Most actionable variants in this cohort were detected in well-established ICC genes, suggesting that large gene panels offer little extra sensitivity compared to historic smaller gene panels. Despite recent gene curation efforts, the high burden of VUS remains a considerable challenge in ICC management. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): National Children's Research Centre